STEP-BY-STEP EXPLOSION SCENE TACTICS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
This article discusses the tactical aspects of examining the scene of an explosion. In this case, the examination of the scene of the incident was divided into three stages: assessment of the initial situation, identification of the center of the explosion, extinguishing, and specific rules for working with the center were analyzed. Also, when inspecting the scene of the explosion, the issues of applying the method of movement at the scene of the explosion to the explosion area are considered. In addition, the issues of taking measurements at the place of the explosion, using technical means during inspection, and the properties of explosives and taking samples were analyzed.